Alternatives to sowing vegetable type soybeans - Mannfredini,Edcarlos (1998)
Today, soybean crops of the Tamba Kurodaisu cultivar are sown in beds prior to transplantation to the field. This planting system has caused crop failure due to damage to the root system. An experiment to test different sowing alternatives to obtain plantlets for cropping of food type big seeded soybean was set up with the following treatments: sowing in beds; sowing in 130 cm³ newspaper cups; sowing in test tubes of volumes of 30 cm³, 60 cm³ and 70 cm³; sowing in 70 cm³ disposable plastic cups; sowing on 90 cm³ styrofoam trays. A randomized complete block design was used, and the following traits were assessed: germination percentage; number of days to flowering; plant height at flowering; number of days to maturity; plant height at maturity; number of seeds per plant; individual plant yield; weight of a hundred seeds. Results should that three methods could be used to set up Tamba Kurodaisu cultivar crops: sowing in disposable plastic cups, sowing in beds with later transplant, or direct sowing in the field.